2018
DOI: 10.2298/jmmb180711016l
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory study on magnetization reduction of CO

Abstract: In this study, magnetizing roasting in fluidized bed was employed to separate iron minerals from red mud. The effect of treatment conditions on product quality was investigated. In addition, the phase transformation, changes in magnetism, and microstructures were studied by thermodynamic analysis, chemical analysis, X-ray diffraction technique (XRD), vibrating sample magnetometer (VSM), and optical microscopy. The magnetic concentrates with the total iron grade of 57.65% and recovery of 90.04% were obtained un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Smelting. Solid state reduction can be conducted as  Carbothermic reduction using a certain type of carbon source [6], conventional process for pig iron making  Reduction roasting, using certain additive(s) in addition to a carbon source [7][8][9][10][11][12][13]  Gaseous reduction using H2 and/or CO or certain gas mixtures [14][15][16][17]  Microwave heating applications [18][19][20] Keskinkilic et al [21] reviewed those examples, so more details can be found in the related literature. The authors have performed a laboratory-scale project dealing with stepwise recovery of valuable elements from red mud.…”
Section: Introductionmentioning
confidence: 99%
“…Smelting. Solid state reduction can be conducted as  Carbothermic reduction using a certain type of carbon source [6], conventional process for pig iron making  Reduction roasting, using certain additive(s) in addition to a carbon source [7][8][9][10][11][12][13]  Gaseous reduction using H2 and/or CO or certain gas mixtures [14][15][16][17]  Microwave heating applications [18][19][20] Keskinkilic et al [21] reviewed those examples, so more details can be found in the related literature. The authors have performed a laboratory-scale project dealing with stepwise recovery of valuable elements from red mud.…”
Section: Introductionmentioning
confidence: 99%